Wacana Lingkungan dan Pembangunan Berkelanjutan dalam Lembaga Swadaya Masyarakat di Indonesia - Nanang Indra Kurniawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
Environmental issues have been largely discussed in development discourse since early 1970s, which have led to the idea of Sustainable Development. Despite of its importance, the debate on environment has been occupied by a tendency to put ‘nature’ and ‘human’ as well as ‘crisis of nature’ and ‘crisis of justice’ in static dichotomies. This article challenges this idea by arguing that the most central matter in environment and development discourses does not lie on ‘human’ and ‘nature’ per se but on the relationship between the two. The challenge of sustainable development is to continuously redefine relationships between human and nature. Using analytical frameworks of Dryzek (1997) and Nygren (1998) this article emphasizes the articulation of discourse repertoires by drawing on a case study among Indonesian environmental Non-Governmental Organizations (NGOs). This study finds out that Indonesian environmental NGOs often incorporate elements of various discourses. This phenomenon shows that environmental NGOs actively involve in the process of negotiation to redefine new borders of sustainable development in Indonesia.